2004
DOI: 10.1038/nature03076
|View full text |Cite
|
Sign up to set email alerts
|

A pancreatic islet-specific microRNA regulates insulin secretion

Abstract: MicroRNAs (miRNAs) constitute a growing class of non-coding RNAs that are thought to regulate gene expression by translational repression. Several miRNAs in animals exhibit tissue-specific or developmental-stage-specific expression, indicating that they could play important roles in many biological processes. To study the role of miRNAs in pancreatic endocrine cells we cloned and identified a novel, evolutionarily conserved and islet-specific miRNA (miR-375). Here we show that overexpression of miR-375 suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
1,511
6
23

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,914 publications
(1,579 citation statements)
references
References 29 publications
39
1,511
6
23
Order By: Relevance
“…MiRNAs play important roles in the development, differentiation, metabolism, cell growth and death in animals and plants (Poy et al, 2004;Cheng et al, 2005;Dresios et al, 2005). There is also evidence that supports a role for miRNAs in hematopoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs play important roles in the development, differentiation, metabolism, cell growth and death in animals and plants (Poy et al, 2004;Cheng et al, 2005;Dresios et al, 2005). There is also evidence that supports a role for miRNAs in hematopoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…The initial paper reporting the first cloning effort of miRNAs in the pancreatic β-cell identified 67 unique sequences including miR-375 [5]. As current sequencing technologies have long rendered this cloning method obsolete, they have also revealed the potential for hundreds of unique functional sequences to be present in most cell types including the β-cell.…”
Section: Microrna Profiling In the Pancreatic β-Cell And Isletsmentioning
confidence: 99%
“…The chronic hyperglycemia characteristic of diabetes has long been established the result of inadequate insulin action making one of the prime directives of the β-cell field to identify genes and mechanisms which contribute to reduced growth and function of this cell type. Since the first gain and loss of function studies on miR-375, several subsequent reports have identified a number of additional miRNAs as negative regulators of β-cell function including miR-7, miR-184, miR-21, miR-29a and miR-33a [5] [12] [8] [17] [18]. Importantly, the role of several miRNAs as negative regulators has been substantiated using specific genetic mouse knockouts [19].…”
Section: Microrna Profiling In the Pancreatic β-Cell And Isletsmentioning
confidence: 99%
“…Regardless of the deficiency in three different hormones in df/df mice, GH seems to be a main regulator of lifespan in healthy animals. These hormonal alterations may play important role in the patterns of circulating miRNAs reported in the present study, as it has been previously shown that groups of miRNA may regulate or are regulated by endocrine signals (Poy et al ., 2004). We previously showed altered patterns and regulations of liver miRNA in Ames dwarf mice (Bates et al ., 2010); however, in the present study we examined circulating miRNA in young and old df/df and normal mice.…”
Section: Introductionmentioning
confidence: 99%